Cancer cell invasion alters the protein profile of extracellular vesicles - Jens C. Luoto; Leila S. Coelho‐Rato; Cecilia Jungarå; Sara H. Bengs; Jannica Roininen; John E. Eriksson; Lea Sistonen; Eva Henriksson (Journal of Extracellular Biology, 2023)
Abstract Extracellular vesicles (EVs) are important mediators of intercellular communication involved in local and long‐range signalling of cancer metastasis. The onset of invasion is the key step of the metastatic cascade, but the secretion of EVs has remained unexplored at that stage due to technical challenges. In this study, we present a platform to track EVs over the course of invasive development of human prostate cancer cell (PC3) tumoroids utilizing in vivo‐mimicking extracellular matrix‐based 3D cultures. Using this EV production method, combined with proteomic profiling, we show that PC3 tumoroids secrete EVs with previously undefined protein cargo. Intriguingly, an increase in EV amounts and extensive changes in the EV protein composition were detected upon invasive transition of the tumoroids. The changes in EV protein cargo were counteracted by chemical inhibition of invasion. These results reveal the impact of the tumoroids’ invasive status on EV secretion and cargo, and highlight the necessity of in vivo‐mimicking conditions for uncovering novel cancer‐derived EV components.